2017
DOI: 10.3390/ijms18010124
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic, Lipid Normalizing, and Nephroprotective Actions of the Strawberry: A Potent Supplementary Fruit

Abstract: The study was designed to assess the effect of different strawberry extracts on glucose levels, lipid profiles, and oxidative stress in nicotinamide-streptozotocin (NIC-STZ) induced diabetic rats. The associated changes were evaluated through biochemical, molecular, and histological assays. Diabetes was induced by intraperitoneal injection of STZ to albino Wistar rats after treatment with nicotinamide. Aqueous, hydroalcoholic, and alcoholic strawberry extracts were administrated orally to diabetic rats. Treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 76 publications
0
21
0
1
Order By: Relevance
“…Oral administration of strawberry leaf extract decreases the serum levels of TNF-α in a rat model of diabetic nephropathy [ 56 ]. Oral administration of different strawberry extracts down-regulated the expression of TNF-α in nicotinamide–streptozotocin-induced diabetes in rats [ 57 ]. Furthermore, we previously showed that the methanolic extract of strawberry effectively attenuated cadmium-induced inflammation in liver [ 21 ], kidney [ 5 ], and testis [ 22 ] tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of strawberry leaf extract decreases the serum levels of TNF-α in a rat model of diabetic nephropathy [ 56 ]. Oral administration of different strawberry extracts down-regulated the expression of TNF-α in nicotinamide–streptozotocin-induced diabetes in rats [ 57 ]. Furthermore, we previously showed that the methanolic extract of strawberry effectively attenuated cadmium-induced inflammation in liver [ 21 ], kidney [ 5 ], and testis [ 22 ] tissues.…”
Section: Discussionmentioning
confidence: 99%
“…integrin-linked kinase, EMT, MMP-9/TIMP-1 ratio [127] ( 10 Journal of Diabetes Research 12 Journal of Diabetes Research ↓: decreased/prevented the increase (of activity (for enzymes)/level (for biochemical parameters))/inhibited/inactivated/blocked/suppressed/downregulated (about pathways, enzymes, receptors, cytokines, etc. ); ↑: increased/prevented the decrease (of activity (for enzymes)/level (for biochemical parameters))/stimulated/activated/upregulated; →: [172], Chlorella pyrenoidosa [173], Cladophora glomerata [34], Coccinia indica [111], coconut water [61], Cordyceps militaris [114], Cornus officinalis [47], curcumin [79], dihydroquercetin [48], Dioscorea bulbifera [96], diosgenin [62], ellagic acid [37], emodin § [94], Flammulina velutipes [53], Fragaria × ananassa [89], Huangqi decoction [36], Hypericum perforatum [31], Paederia foetida [78], Paeonia emodi [63], palm oil and rice bran oil [50], Panax notoginseng [35], Panax quinquefolium [82], Panax quinquefolium [83], Physalis angulata [64], Pleurotus eryngii polysaccharides [57], Prunella vulgaris [84], Punica granatum [32], quercetin [49], Ramulus mori [77], Rheum ribes [175], secoisolariciresinol diglucoside [88], Spirogyra neglecta [176], Tangke decoction [116], Terminalia chebula [33] Insulin resistance…”
Section: In Vitro Studies-potentially Nephroprotectivementioning
confidence: 99%
“…Enzim ppar-γ bekerja memproduksi rna messenger yang akan membentuk glut4. Pembentukan glut 4 yang lebih banyak akan menyebabkan glukosa yang masuk dalam sel semakin banyak [27], [28]. Asam klorogenat juga mampu mencegah dan mengobati penyakit kronis metabolik, seperti sindrom metabolik dan diabetes tipe 2 [29].…”
Section: Pengamatan Manifestasi Klinikunclassified